2018
DOI: 10.3892/or.2018.6246
|View full text |Cite
|
Sign up to set email alerts
|

β‑carotene reverses tobacco smoke‑induced gastric EMT via Notch pathway in vivo

Abstract: Tobacco smoke is one of the serious risk factors of gastric cancer. Epithelial‑mesenchymal transition (EMT) has been shown to be associated with the initiation and carcinogenesis of gastric cancer. The role of Notch pathway in regulating tobacco smoke-induced EMT has not been investigated. β‑carotene, a carotenoid present in fruits, vegetables and rice, suppresses cancer progression. In this investigation, we evaluated the regulatory role of Notch pathway in tobacco smoke‑mediated gastric EMT and the preventiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Also, Cur works synergistically with different antimicrobials including oxacillin, ciprofloxacin, and norfloxacin against multi‐resistant microscopic organisms . Another in vitro examination suggests that Cur in combination synergistically increases the anti‐tumor effect of various anticancer agents …”
Section: Introductionmentioning
confidence: 99%
“…Also, Cur works synergistically with different antimicrobials including oxacillin, ciprofloxacin, and norfloxacin against multi‐resistant microscopic organisms . Another in vitro examination suggests that Cur in combination synergistically increases the anti‐tumor effect of various anticancer agents …”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry was performed to detect the expression of E-cadherin and vimentin as previous described. 26 …”
Section: Methodsmentioning
confidence: 99%
“…The epithelial-mesenchymal transition is involved in the initiation of tumorigenesis. In the study mentioned above, researchers found that tobacco smoke-induced gastric epithelial-mesenchymal transition was associated with the Notch pathway, but beta-carotene effectively attenuated this process in the mouse stomach[ 100 ]. Beta-carotene can prevent the occurrence of gastric cancer through these mechanisms, which are summarized in Figure 4 .…”
Section: The Mechanism By Which Of Beta-carotene Modulates Gastric Cancermentioning
confidence: 99%